Prolapse of the posterior leaflet: resect or respect - Perier, Patrick; Hohenberger, Wolfgang; Lakew, Fitsum; Diegeler, Anno (Annals of Cardiothoracic Surgery, 2015)
Prolapse of the posterior leaflet (PPL) is the most frequent dysfunction of the mitral valve in the western world. Quadrangular resection, first proposed by Alain Carpentier, has progressed to become the gold standard modality to repair posterior leaflet prolapse. Although this “resection technique” is safe, reproducible, and offers favorable long term results, it presents major drawbacks. Firstly, it leads to a reduced surface of coaptation, the ultimate goal of mitral valve repair; secondly, it does not respect the anatomy of the mitral valve; thirdly, it leads to a deformation of the base of the ventricle; and finally, degenerative disease of the mitral valve is a spectrum of lesions depending on the amount of excess tissue, and hence, a one technique-fits-all strategy cannot meet the absolute necessity to repair all mitral valve patients with PPL. Therefore, new approaches which have been proposed place greater emphasis on respecting, rather than only resecting, the leaflet tissue in order to avoid the drawbacks of the “resection” approach. The use of artificial chordae to correct the leaflet prolapse restores the normal anatomy and physiology of the mitral valve, thus producing an optimal surface of coaptation. However, this approach is limited by anatomical variances. As a community, we should expand our vision and define a clear and helpful strategy for PPL: to obtain a high, smooth and regular surface of coaptation located in the inflow of the left ventricle. To achieve this goal, it is necessary to have a high level of respect for the leaflet tissue in order to obtain the best surface of coaptation. Nonetheless, a limited resection may be needed to remodel the posterior leaflet, so that it will be smooth and regular.